Alternative Industry Performance and Risk - Reilly, Frank K.; Drzycimski, Eugene F. (Journal of Financial and Quantitative Analysis, 1974)
Industry analysis has long been a cornerstone in both the academic and professional segments of the investment community. Concepts such as “an industry providing downside protection” or “another is certain to outperform the market” have been prevalent throughout the profession. The importance of industry analysis in terms of stock price changes has been suggested by King, while the influence of the industry factor on corporate earnings changes has been documented by Brown and Ball. These studies and others have indicated that industry analysis has been an important part of security valuation.